e-Procurement Management Practices and Procurement Performance of some Selected public Hospitals in Lagos State, Nigeria: The Mediating Role of Supply Chain Performance. - Kazeem, Yusau; Olatunji, Dr Olabode; Olakunle, Jayeola (International Journal of Scientific Research and Management (IJSRM), 2025)
The study investigated the mediating influence of supply chain performance on the association of e-procurement management practices and procurement performance of Public hospitals in Lagos state, The study employed descriptive research design. Primary data were gathered through administration of questionnaire. In selecting ample size, multi-stage sampling technique was adopted for the study. First stage used a census survey to select 5 public hospitals comprising Federal Medical Center, Specialist Hospitals and University Teaching Hospitals in Lagos state. The second stage involved the selection of respondents from the units such as: account, internal audit, store, ICT, procurement office, supply chain Mangers, general administration, pharmacy and procurement committee chair in each of the 5 hospitals purposively selected for this study totaling 50 respondents. Data obtained were analysed using structural equation modelling (SEM). The findings showed that supply chain performance mediated the relationship between e-procurement management practices and procurement performance of the selected hospitals in Lagos state.